Preparation method of cubic-phase lithium lanthanum zirconium oxide solid electrolyte
By controlling the reaction conditions and process steps, the stable cubic phase lithium lanthanum zirconium oxygen (LLZO) solid electrolyte was successfully synthesized at a lower sintering temperature, solving the problem of structural instability in the prior art and significantly improving the lithium ion conduction performance, the safety and energy density of the battery.
Patent Information
- Application Number
- CN202510162218.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to effectively stabilize the solid electrolyte structure of cubic phase lithium lanthanum zirconium oxygen (LLZO), affecting its ionic conductivity and its safety and energy density applied to all-solid-state lithium-ion batteries.
By controlling the reactant concentration, temperature, stirring speed and time, the metal salt solution and the precipitant solution were respectively arranged, and a co-precipitation reaction was carried out to obtain a metal oxide precursor. Then, a stable cubic phase LLZO solid electrolyte was modified and sintered by rotary evaporation and high-temperature heat treatment.
The successful synthesis of stable cubic phase LLZO materials under lower sintering temperature conditions significantly improves lithium ion conduction performance, enhances battery safety and energy density, and reduces production energy consumption.
Smart Images

Figure CN119920954A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of solid electrolytes and solid lithium ion batteries, and in particular relates to a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte. Background Art
[0002] Garnet-type lithium lanthanum zirconium oxide (Li 7 La 3 Zr 2 O 12 , LLZO) solid electrolytes are considered to be highly promising candidate materials for all-solid-state lithium-ion batteries due to their excellent ionic conductivity, outstanding electrochemical stability, and good chemical compatibility with positive electrode and lithium metal negative electrode materials. This type of battery is known for its high safety, high energy density, and long life, and represents the development direction of future electrochemical energy storage technology.
[0003] LLZO can present two different crystal structures: cubic phase (c-LLZO) and tetragonal phase (t-LLZO). The difference between the two is mainly reflected in the position of lithium ions - in the cubic phase, lithium ions partially occupy the interstitial positions; in the tetragonal phase, these positions are completely filled with lithium ions. In contrast, cubic phase LLZO exhibits higher ionic conductivity, thanks to its unique crystal skeleton network, in which La³⁺, Zr 4 The ⁺ and O²⁻ ions build a stable framework that allows lithium ions to move freely inside it. This structure ensures the shortest distance between adjacent lithium ions, thereby promoting fast ion transport and giving c-LLZO excellent ion conductivity.
[0004] In order to maintain and optimize the ionic conductivity characteristics of LLZO, stabilizing its cubic phase structure has become the focus of research. Therefore, in view of the above situation, it is urgent to develop a preparation method for cubic lithium lanthanum zirconium oxygen solid electrolyte to overcome the shortcomings in current practical applications. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a cubic phase lithium lanthanum zirconium oxide solid electrolyte. The prepared cubic phase lithium lanthanum zirconium oxide solid electrolyte powder can be used to develop polymer solid electrolyte additives, solid electrolyte slurries, solid electrolyte films, solid electrolyte blocks, etc., and to develop high-safety, high-energy density, long-life semi-solid or solid-state lithium-ion batteries to solve the problems mentioned in the above background technology.
[0006] The present invention is achieved by a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, comprising the following steps: Step 1: respectively prepare a metal salt solution and a precipitant solution in a reaction kettle, and respectively obtain a uniformly dispersed metal salt solution and a precipitant solution by controlling the concentration of reactants, temperature, stirring speed and time; Step 2: adding the metal salt solution and the precipitant solution into another reactor at a certain flow rate at the same time, setting a specified stirring speed, insulation temperature and insulation time in the reactor to obtain a metal oxide co-precipitation precursor mixed solution; Step 3: removing water from the mixed solution of the metal oxide co-precipitation precursor by a solid-liquid separation process, and continuing to add pure water to wash the precipitate, and obtaining the metal oxide co-precipitation precursor by solid-liquid separation; Step 4: obtaining a metal oxide precursor and an organic solvent by solid-liquid separation in a rotary evaporator, and removing water from the precursor precipitate by a rotary evaporation process, while modifying the surface of the precursor particles; Step 5: placing the powder obtained after rotary evaporation into a high-temperature furnace for heat treatment to obtain metal oxide; Step 6: Add lithium source and dopant to the metal oxide obtained by heat treatment, mix the powder evenly by ball milling, press the powder into blocks, and then place the block sample in a high-temperature furnace and sinter under certain temperature, pressure and atmosphere conditions to obtain a cubic lithium lanthanum zirconium oxygen solid electrolyte.
[0007] A further technical solution is that in step one, the metal element in the metal salt solution is one or more of lanthanum, zirconium, aluminum, gallium, niobium, titanium, and tantalum, and may be a soluble nitrate, chloride, or the like; the precipitant solution is one or more of a soluble hydroxide alkaline solution and a soluble carbonate solution, and may be a sodium hydroxide solution, a potassium hydroxide solution, an ammonia solution, a sodium carbonate solution, a sodium bicarbonate solution, a potassium carbonate solution, a potassium bicarbonate solution, or the like.
[0008] According to a further technical solution, the stirring speed in step 2 is 20 to 100 rpm, the reaction temperature is 20 to 60° C., and the insulation time is 0.1 to 3 hours, depending on the type and concentration of the precursor metal salt solution and the precipitant solution.
[0009] According to a further technical solution, in step three, the solid-liquid separation process is one or more of vacuum filtration, centrifugal separation, extrusion separation, and gravity sedimentation.
[0010] According to a further technical solution, in step 4, the organic solvent is one or more of ethanol, n-hexane, n-pentanol, acetic acid, petroleum ether and chloroform.
[0011] According to a further technical solution, in step five, the heat treatment temperature is 400 to 900° C. and the heat preservation time is 1 to 5 hours, depending on the chemical composition of the metal oxide precursor.
[0012] According to a further technical solution, in step six, the lithium source is a lithium compound, specifically one or more of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium chloride, and lithium oxide.
[0013] According to a further technical solution, in step six, the dopant is a compound of metal elements such as niobium, tantalum, aluminum, gallium, and germanium, specifically one or more of metal oxides, metal hydroxides, and metal carbonates.
[0014] According to a further technical solution, in step six, the sintering temperature is 900-1200°C, the holding time is 6-24 hours, the ambient pressure is atmospheric pressure or 1-10 MPa under hot pressing sintering, and the reaction atmosphere is air, air without moisture and carbon dioxide, argon or nitrogen.
[0015] The present invention provides a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, which has the following beneficial effects: 1) The present invention can successfully synthesize a stable cubic phase structure lithium lanthanum zirconium oxide (LLZO) solid electrolyte material under low sintering temperature conditions, which not only helps to reduce energy consumption, but also avoids the volatilization problem of lithium compounds during high temperature treatment, thereby being more conducive to the implementation of large-scale production; 2) The obtained cubic phase LLZO material exhibits excellent lithium ion conductivity, which plays an important role in promoting the development of solid electrolytes and all-solid-state lithium batteries; 3) The prepared micro-nano cubic phase LLZO solid electrolyte can be used as an additive in polymer solid electrolytes, which can effectively improve the ion conduction efficiency, thermal stability and overall safety of the polymer matrix; 4) This material can be used as a surface modifier for polyolefin separators to enhance the heat resistance of the separators and further strengthen the safety of the batteries; 5) This micro-nano cubic phase LLZO can be used for surface modification of positive electrode materials to improve the ionic conductivity of positive electrode materials and thus optimize the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Schematic diagram of X-ray diffraction analysis (XRD) of metal oxide precursor; Figure 2 Schematic diagram of X-ray diffraction analysis (XRD) of metal oxide precursor after high temperature heat treatment; Figure 3 Schematic diagram of X-ray diffraction analysis (XRD) of lithium lanthanum zirconium oxygen solid electrolyte sample prepared by sintering. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0018] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0019] Example 1
[0020] like Figure 1-3 As shown, a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte is provided in one embodiment of the present invention, wherein the solid electrolyte is a tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0021] The preparation steps of the above solid electrolyte are as follows: using lanthanum chloride as a lanthanum source and zirconium oxychloride as a zirconium source, a special precipitation reaction is used to prepare hydroxide precursor precipitates of lanthanum oxide and zirconium oxide respectively, and then a centrifuge is used for solid-liquid separation, and the precipitate is washed with pure water. The precipitate analysis test results are as follows: Figure 1 and Figure 2 shown.
[0022] Then, an organic solvent is added to the precursor precipitate, residual water in the precipitate is removed by a rotary evaporator, and the precipitate powder is surface modified.
[0023] The powder material obtained by rotary evaporation was kept at 500° C. in a high-temperature furnace for 3 hours to prepare highly dispersed lanthanum oxide and zirconium oxide micro-nano powders.
[0024] According to the experimental design, the prepared lanthanum oxide and zirconium oxide were weighed, a certain amount of lithium carbonate and tantalum oxide were added, the powder materials were mixed evenly using a ball mill, the powders were pressed into dense blocks using a press, and then placed in a high-temperature furnace, and calcined at high temperature in a closed crucible at a sintering temperature of 1050°C for 12 hours to obtain a cubic phase tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material, such as Figure 3 shown.
[0025] Example 2
[0026] An embodiment of the present invention provides a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, wherein the solid electrolyte is a tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0027] The preparation steps of the above-mentioned solid electrolyte are as follows: using lanthanum chloride as a lanthanum source and zirconium chloride as a zirconium source, a coprecipitation reaction is used to prepare a hydroxide precursor precipitate mixture of zirconium oxide and lanthanum oxide, and then a vacuum filter is used for solid-liquid separation, and the precipitate mixture is washed with pure water.
[0028] Then, an organic solvent is added to the precursor precipitate mixture, residual water in the coprecipitate is removed by a rotary evaporator, and the coprecipitate powder is surface modified.
[0029] The powder material obtained by rotary evaporation was kept at 750° C. in a high-temperature furnace for 2 hours to prepare a highly dispersed zirconium oxide and lanthanum oxide micro-nano powder mixture.
[0030] According to the experimental design, a certain amount of the above-mentioned zirconium oxide and lanthanum oxide mixture is weighed, a certain amount of lithium hydroxide and tantalum oxide is added, the powder materials are mixed evenly using a ball mill, the powder is pressed into a dense block using a press, and then placed in a high-temperature furnace, and high-temperature calcined in a closed crucible at a sintering temperature of 1100°C. The material is kept warm for 12 hours to obtain a cubic phase tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0031] Example 3
[0032] An embodiment of the present invention provides a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, wherein the solid electrolyte is a tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0033] The preparation steps of the above-mentioned solid electrolyte are as follows: lanthanum nitrate is used as a lanthanum source and zirconium nitrate is used as a zirconium source, and a special precipitation reaction is used to prepare hydroxide precursor precipitates of lanthanum oxide and zirconium oxide respectively, and then a vacuum filter is used for solid-liquid separation, and the precipitate mixture is washed with pure water.
[0034] Then, an organic solvent is added to the precursor precipitate, residual water in the precipitate is removed by a rotary evaporator, and the precipitate powder is surface modified.
[0035] The powder material obtained by rotary evaporation was kept at 700° C. in a high-temperature furnace for 3 hours to prepare highly dispersed zirconium oxide and lanthanum oxide micro-nano powders.
[0036] According to the stoichiometric ratio, a certain amount of the above-mentioned zirconium oxide and lanthanum oxide are weighed respectively, a certain amount of lithium hydroxide and tantalum oxide are added, the powder materials are mixed evenly using a ball mill, the powder is pressed into a dense block using a press, and then placed in a high-temperature furnace, and high-temperature calcined in a closed crucible at a sintering temperature of 1100°C and kept warm for 12 hours to obtain a cubic phase tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0037] Example 4
[0038] An embodiment of the present invention provides a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, wherein the solid electrolyte is a tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0039] The preparation steps of the above-mentioned solid electrolyte are as follows: using lanthanum nitrate as a lanthanum source and zirconium nitrate as a zirconium source, a co-precipitation reaction is used to prepare a hydroxide precursor precipitate mixture of zirconium oxide and lanthanum oxide, and then a centrifuge is used for solid-liquid separation, and the precipitate mixture is washed with pure water.
[0040] Then, an organic solvent is added to the precursor precipitate mixture, residual water in the coprecipitate is removed by a rotary evaporator, and the coprecipitate powder is surface modified.
[0041] The material obtained by rotary evaporation was kept at 750° C. in a high-temperature furnace for 2 hours to prepare a highly dispersed mixture of zirconium oxide and lanthanum oxide micro-nano powders.
[0042] According to the experimental design, a certain amount of the above-mentioned zirconium oxide and lanthanum oxide mixture is weighed, a certain amount of lithium carbonate and tantalum oxide is added, the powder materials are mixed evenly using a ball mill, the powder is pressed into a dense block using a press, and then placed in a high-temperature furnace, and high-temperature calcined in a closed crucible at a sintering temperature of 1050°C. The material is kept warm for 12 hours to obtain a cubic phase tantalum-doped lithium lanthanum zirconium oxygen solid electrolyte material.
[0043] The above embodiment of the present invention provides a method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, the main advantages of which are as follows: 1) The present invention can successfully synthesize a stable cubic phase structure lithium lanthanum zirconium oxide (LLZO) solid electrolyte material under low sintering temperature conditions, which not only helps to reduce energy consumption, but also avoids the volatilization problem of lithium compounds during high temperature treatment, thereby being more conducive to the implementation of large-scale production; 2) The obtained cubic phase LLZO material exhibits excellent lithium ion conductivity, which plays an important role in promoting the development of solid electrolytes and all-solid-state lithium batteries; 3) The prepared micro-nano cubic phase LLZO solid electrolyte can be used as an additive in polymer solid electrolytes, which can effectively improve the ion conduction efficiency, thermal stability and overall safety of the polymer matrix; 4) This material can be used as a surface modifier for polyolefin separators to enhance the heat resistance of the separators and further strengthen the safety of the batteries; 5) This micro-nano cubic phase LLZO can be used for surface modification of positive electrode materials to improve the ionic conductivity of positive electrode materials and thus optimize the overall performance of the battery.
[0044] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0045] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a cubic lithium lanthanum zirconium oxygen solid electrolyte, characterized in that: The following steps are involved: Step 1: respectively prepare a metal salt solution and a precipitant solution in a reaction kettle, and respectively obtain a uniformly dispersed metal salt solution and a precipitant solution by controlling the concentration of reactants, temperature, stirring speed and time; Step 2: adding the metal salt solution and the precipitant solution into another reactor at a certain flow rate at the same time, setting a specified stirring speed, insulation temperature and insulation time in the reactor to obtain a metal oxide co-precipitation precursor mixed solution; Step 3: removing water from the mixed solution of the metal oxide co-precipitation precursor by a solid-liquid separation process, and continuing to add pure water to wash the precipitate, and obtaining the metal oxide co-precipitation precursor by solid-liquid separation; Step 4: obtaining a metal oxide precursor and an organic solvent by solid-liquid separation in a rotary evaporator, and removing water from the precursor precipitate by a rotary evaporation process, while modifying the surface of the precursor particles; Step 5: placing the powder obtained after rotary evaporation into a high-temperature furnace for heat treatment to obtain metal oxide; Step 6: Add lithium source and dopant to the metal oxide obtained by heat treatment, mix the powder evenly by ball milling, press the powder into blocks, and then place the block sample in a high-temperature furnace and sinter under certain temperature, pressure and atmosphere conditions to obtain a cubic lithium lanthanum zirconium oxygen solid electrolyte.
2. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: In step one, the metal element in the metal salt solution is one or more of lanthanum, zirconium, aluminum, gallium, niobium, titanium, and tantalum; and the precipitant solution is one or more of soluble hydroxide alkaline solution and soluble carbonate solution.
3. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 2, characterized in that: According to the types and concentrations of the precursor metal salt solution and the precipitant solution, the stirring speed in step 2 is 20 to 100 rpm, the reaction temperature is 20 to 60° C., and the insulation time is 0.1 to 3 hours.
4. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 1, characterized in that: In step three, the solid-liquid separation process is one or more of vacuum filtration, centrifugal separation, extrusion separation, and gravity sedimentation.
5. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 2, characterized in that: In step 4, the organic solvent is one or more of ethanol, n-hexane, n-pentanol, acetic acid, petroleum ether and chloroform.
6. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 5, characterized in that: In step five, according to the different chemical compositions of the metal oxide precursor, the heat treatment temperature is 400-900° C. and the heat preservation time is 1-5 hours.
7. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to any one of claims 1 to 6, characterized in that: In step six, the lithium source is a lithium compound, specifically one or more of lithium hydroxide, lithium hydroxide monohydrate, lithium carbonate, lithium chloride, and lithium oxide.
8. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 7, characterized in that: In step six, the dopant is a compound of metal elements such as niobium, tantalum, aluminum, gallium, and germanium, specifically one or more of metal oxides, metal hydroxides, and metal carbonates.
9. The method for preparing the cubic lithium lanthanum zirconium oxygen solid electrolyte according to claim 8, characterized in that: In step six, the sintering temperature is 900-1200° C., the holding time is 6-24 hours, the ambient pressure is atmospheric pressure or 1-10 MPa under hot pressing sintering, and the reaction atmosphere is air, air dehydrated with water and carbon dioxide, argon or nitrogen.
Citation Information
Cited By
Nanometer cubic-phase lithium lanthanum zirconium oxide, preparation method thereof and solid electrolyte
CN120440949A
A nano cubic phase lithium lanthanum zirconium oxide and its preparation method and solid electrolyte
CN120440949B
Preparation method of lithium lanthanum zirconium oxide solid electrolyte doped with aluminum element
CN121507129A